1-Ethyl-6-fluoro-7-(4-methylpiperazin-4-ium-1-yl)-4-oxo-1,4-dihydroquinoline-3-carboxylate hexahydrate - An, Zhe (International Union of Crystallography, 2008)
In the title compound, C(17)H(20)FN(3)O(3)·6H(2)O, the pefloxacin (pef) neutral zwitterion is accompanied by six water molecules of hydration. An extensive network of O—H⋯O and N—H⋯O hydrogen bonds help to establish the crystal packing.